THE EFFECT OF COORDINATION FUNCTIONS ON EMPLOYEE EFFECTIVENESS AT THE REGIONAL SECRETARIAT OF OKU EAST REGENCY - Erwin, Ripda (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The interaction between various resources must be managed properly so that it can achieve the target effectively and efficiently through good coordination between the leadership and employees as well as between the employees themselves. Likewise, the problem faced by the Regional Secretariat of East OKU Regency is how the effect of the coordination function on the effectiveness of the work of employees, while the purpose of this study is to determine the effect of the coordination function on the effectiveness of the work of employees at the Regional Secretariat of East OKU Regency. The hypothesis proposed is that the coordination function has a strong effect on the work effectiveness of employees at the Regional Secretariat of East OKU Regency. From the calculation results obtained r = 0.099, after consulting with a conservative standard, it turns out that 0.099 lies between 0.000 - 0.199 which is included in the very low correlation. So it can be said that there is a very low influence between the coordination function on the work effectiveness of employees at the Regional Secretariat of East OKU Regency. Then to answer the hypothesis test proposed in the previous chapter has a relationship or not, then it is tested with a hypothesis test and obtained (t) table = 1.860, while (t) count = 0.280 which can be concluded that (t) count < (t) table or ( t arithmetic is smaller than t table ), so that the hypothesis proposed in the previous chapter cannot be accepted and is not proven. Key Word : Coordination Function; Wor;k Effectiveness